Mengidentifikasi Faktor Penghambat Guru Matematika Kecamatan Dompu NTB Terhadap Proses Pembelajaran pada Sekolah Menengah Atas - Muh Fitrah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2015)
The purpose of this research is to identify an inhibiting factor of teachers and to seek a solution in mathematics learning process at senior high school in Dompu NTB. This is a qualitative-descriptive research. The subject of this research is five mathematics teachers who spread out at five high schools. Research data is gained by a means of: 1) a field note; 2) interview; 3) questionnaire, & 4) document. Datum analysis technique uses descriptive qualitative. The result of this research shows that the inhibiting factor of the teacher s in mathematics learning process: 1) students, low basic knowledge on mathematics concept they have, specially lack of mastering a basic subject; 2) teachers, the teachers only tend to teach the basic matter on mathematics concept; 3) learning process , teachers’ low motivation in combining and implementing various models of learning approach which make the students miss mathematics; 4) a learning evaluation, lack of teacher’s skill and knowledge in designing the learning evaluation instrument, and 5) a learning means and instrument, no proper media of mathematics learning at schools, no creativity, no innovation, and no teaching art of teachers in arranging the learning media.